Research on Chinese well-known e-commerce enterprises' innovation ability based on real comment. (27th February 2020) - Li, Shufang; Jiang, Changbing; Li, Liang
Based on the real comments from Jingdong Mall, T-mall and other e-commerce platforms as for the data resource, according to analysis to the customers' online shopping comments' vocabularies, obtained 11 indicators which are constituted e vocabularies, obtained 11 indicators which are constituted e-commerce platform customer satisfaction index system and the satisfaction indicator value, using projection pursuit model (PPM) and genetic algorithms to make a further calculation to satisfaction indicators. The results show that: which has the greatest impact on e-commerce platforms' overall satisfaction is the product reputation and popularity; Jingdong Mall has the best overall satisfaction among Jingdong Mall, T-mall, and Amazon this three e-commerce platforms. Meanwhile, each ecommerce platforms has its own superiority and own superiority and weakness.